Uncertainties in the measurements of water-soluble organic nitrogen in the aerosol. (November 2016) - Matsumoto, Kiyoshi; Yamato, Koki
Abstract: In order to evaluate the positive and negative artifacts in the measurements of the water-soluble organic nitrogen (WSON) in the aerosols by filter sampling, comparative experiments between the filter sampling and denuder-filter sampling were conducted during both the warm and cold seasons. The results suggest that the traditional filter sampling underestimates the concentrations of the particulate WSON due to its volatilization loss, but this effect on the ratio of the WSON to the water-soluble total nitrogen (WSTN) was small probably because inorganic nitrogen species were also lost during the filter sampling. Approximately 32.5% of the WSON in the PM2.5 was estimated to be lost during the filter sampling. The denuder–filter sampling also demonstrated the existence of the WSON in the gas phase with approximately quarter concentrations of the WSON in the PM2.5 . On the other hand, the filter sampling would overestimate the gaseous WSON concentration due to the loss of the WSON from the aerosol collection filter. Highlights: Traditional filter sampling underestimates the WSON concentration in the aerosols. Approximately 32.5% of the WSON in the PM2.5 was lost during the filter sampling. Gaseous WSON showed approximately quarter concentrations of the WSON in the PM2.5 .